Direct synthesis of α-functionalized amides via heteroatom–hydrogen insertion reactions using amide-sulfoxonium ylides - Haiting Wu; Yougen Xu; An Lin; Zhi Wang; Huanjun Chen; Xinwei Zhu; Yadong Gao; Lebin Su (Nature Communications)
Abstract α-Functionalized Si-, Ge-, B-, Se-, and S-amide moieties are present in many medicinally active molecules, but their synthesis remains challenging. Here, we demonstrate a high-throughput synthesis using amide-sulfoxonium ylides as carbene precursors in a Si–H, Ge–H, B–H, Se–H, and S–H insertion reactions to target a wide range of α-silyl, α-geryl, α-boryl, α-selenyl, and α-sulfur (hetero)amides. The process is featured as simple operation, mild conditions, broad substrate scope, high functional group compatibility, and excellent chemoselectivity. Both experimental and computational studies are conducted to explore the mechanisms underlying the formation of C–Si/Ge/B/Se/S bond. This research highlights the use of highly selective X–H insertion reactions with amide-sulfoxonium ylide-derived carbenes, paving the way for the preparation of diverse functional organosilane, organogermane, organoboron, organoselenium, and organosulfur compounds from accessible and bench-stable precursors.